First indications on the development of Myzus persicae (Sulzer) (Rhynchota Aphididae) on different herbaceous species (Bollettino di zoologia agraria e bachicoltura, 2024)
The suitability of fifteen species as hosts for the green peach aphid was evaluated measuring the intrinsic rates of increase (rm) and other biological parameters. The weed species tested (Pisum sativum L., Trifolium repens L. , T. pratense L., Lupinus polyphyllus Lindley, Saponaria ocymoides L., Zinnia elegans L., Taraxacum officinale Weber, Matricaria chamomilla L. , Centaurea cyanus L. , Achillea millefolium L., Bellis perennis L., Amaranthus retroflexus L., Lepidium sativum L., Linum rubrum L., Papaver rhoeas L.) are very diffused in the orchards, hobby gardens and in natural or uncultivated areas ; thus they are potential secondary hosts and a source of infections by the aphids. Experiments were conducted to study, under controlled conditions , the development of M. persicae and the suitability of the plants shown by the aphid. The symptoms caused by its attack on the weed species are also reported. The results have shown that M. persicae has a dissimilar development on the different species and it prefers to grow on some of them as Z. elegans, T. officinale, C. cyanus and A. millefolium. On the contrary L. rubrum, L. polyphyllus and Trifolium spp. were not suitable hosts of M. persicae. Moreover, this study shows that not all plants, even if they could be considered secondary hosts, are negatively affect by the presence of the green peach aphid. The results highlight that many, rather common, spontaneous species could be suitable hosts of M. persicae.